1992
DOI: 10.1177/088626092007001002
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Marital Aggression in a National Sample of Young Men

Abstract: This study examined the relationship between alcohol and individual difference factors on one hand and marital aggression on the other hand. Subjects were 320 married and cohabiting men who participated in a nationally representative study of alcohol consumption in young men. Subjects completed scales assessing hostility, self-consciousness, and marital satisfaction, and the Alcohol Dependence Scale (ADS). They also answered two questions concerning marital aggression: whether they had ever hit their spouse wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(94 citation statements)
references
References 20 publications
5
89
0
Order By: Relevance
“…Indeed, "for every 10 years increase in age, risk of mild male partner aggression decrease[d] by 29% and risk of severe aggression decrease [d] by 19%" (Schumacher et al 2001, p. 286). Research from Leonard and Blane (1992) shows a significant predictor of adult male aggression is being non-White. However, Kantor et al (1994) found that race did not significantly predict intimate partner violence when other factors were controlled.…”
Section: Intimate Partner Violencementioning
confidence: 98%
“…Indeed, "for every 10 years increase in age, risk of mild male partner aggression decrease[d] by 29% and risk of severe aggression decrease [d] by 19%" (Schumacher et al 2001, p. 286). Research from Leonard and Blane (1992) shows a significant predictor of adult male aggression is being non-White. However, Kantor et al (1994) found that race did not significantly predict intimate partner violence when other factors were controlled.…”
Section: Intimate Partner Violencementioning
confidence: 98%
“…Research suggests that anger is a factor in domestic violence (e.g., Leonard & Blane, 1992;Maiuro, Cahn, Vitaliano, Wagner, & Zegree, 1988 victims of rape and IPV) experience intense anger following the crime event. Anger has also been demonstrated to increase the amount of depression and PTSD experienced by victims (Novaco, Hamada, Gross, & Smith, 1997;Resick, 1988).…”
Section: Angermentioning
confidence: 99%
“…The effect of alcohol on domestic violence is moderated by hostility, marital discord, and negative affect (Leonard & Blane, 1992). Where there is hostility, conflict, and bad feeling in any relationship interaction, one response is to take steps to ameliorate the situation through interpersonal problem solving.…”
Section: Drinkingmentioning
confidence: 99%